ANALISIS PENCEGAHAN BAHAYA PADA BENGKEL BUBUT PT HARMAIN (STUDI KASUS: DOCKYARD BALIKPAPAN – MARINE SERVICE SHIPPING PT PERTAMINA (PERSERO) RU V - Pongky, Patunru; Hardiyono, Hardiyono; Purwanti, Sri; Herman, Herman (IDENTIFIKASI, 2023)
Abstrak : Along with the increasing volume of work in the lathe workshop will also increase the risk of accidents that will occur as observed in the turning work. This study aims to determine the level of risk of accidents in the lathe workshop while doing the lathe work. This research is a qualitative research and assessment of the risk level of accidents with risk assessment which in this study refers to ISO 31000. The results showed that the percentage incidence of workplace accidents at the lathe workshop found work turning up ranked first with a percentage of 18.5% and ranking the second is occupied by cutting work using a lathe with an accident percentage of 14.3% with risk ranking and hazard level with a value of 5C / 15. Prevention of results of determination of risk ranking and hazard level for risk assessment identification is emphasized through the approach to improving labor qualifications, tool certification, use of assistive devices and transport, building energy-saving programs, applying SOP and JSA, effective use of PPE and dissemination of HSE implementation